Measurement of the t(t)over-bar production cross section using events in the e mu final state in pp collisions at root s=13 TeV - Khachatryan, V. (2017)
The cross section of top quark-antiquark pair production in proton-proton collisions at root s = 13 TeV is measured by the CMS experiment at the LHC, using data corresponding to an integrated luminosity of 2.2 fb(-1). The measurement is performed by analyzing events in which the final state includes one electron, one muon, and two or more jets, at least one of which is identified as originating from hadronization of a b quark. The measured cross section is 815 +/- 9 (stat) +/- 38 (syst) +/- 19 (lumi) pb, in agreement with the expectation from the standard model.